Growth of a-axis-oriented Al-doped ZnO thin film on glass substrate using unbalanced DC magnetron sputtering. (March 2019) - Aryanto, D; Marwoto, P; Sudiro, T; Wismogroho, A S; Sugianto,
Abstract: Al-doped ZnO (AZO) thin films have been deposited on glass substrates using home-made DC magnetron sputtering at room temperature. The effects of Al-doping and sputtering power on the morphology and structure of AZO thin films were studied. X-ray diffraction shows that all AZO thin films have a polycrystalline nature with a hexagonal wurtzite structure. The preferential orientation planes of (100) and (110) AZO thin films were obtained by adding 2 at% Al-doping and prepared using plasma powers of 30 and 40 Watts. Texture coefficient ( TC ), crystalline size ( D ), lattice strain ( ε ), and lattice constant of the (100) and (110) planes of AZO thin film were calculated. Increasing the plasma power leads to the enhancement of crystal quality, crystalline size and grain size of a -axis orientation. Atomic force microscopy analysis shows that the surface of AZO thin film becomes smoother with increasing the grain size. The growth parameters in the deposition of thin films using sputtering technique have significant effect on morphology and structure of the films.